2017
DOI: 10.1111/imig.12342
|View full text |Cite
|
Sign up to set email alerts
|

Food Security at Whose Expense? A Critique of the Canadian Temporary Farm Labour Migration Regime and Proposals for Change

Abstract: Temporary farm labour migration schemes in Canada have been justified on the premise that they bolster food security for Canadians by addressing agricultural labour shortages, while tempering food insecurity in the Global South via remittances. Such appeals hinge on an ideology defining migrants as racialized outsiders to Canada. Drawing on qualitative interviews and participant observation in Mexico, Jamaica and Canada, we critically analyse how Canada's Seasonal Agricultural Worker Program is tied to ideolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(37 citation statements)
references
References 41 publications
1
33
0
3
Order By: Relevance
“…He reasons that because farm employers have become structurally dependent on the SAWP, it is necessary to continue the program and reduce regulatory requirements that employers experience as a bureaucratic hassle. This frame echoes employer and agriculture industry claims documented in other studies, namely, the idea that farms and domestic food security would collapse without the SAWP (Weiler et al 2017 ). Such claims of exceptionalism and urgency underpin the premise that unfree labour migration programs are the only means to uphold public goods like food security, and that these programs should consequently be “made even more employer-friendly” (Binford 2013 , p. 193).…”
Section: Resultssupporting
confidence: 72%
“…He reasons that because farm employers have become structurally dependent on the SAWP, it is necessary to continue the program and reduce regulatory requirements that employers experience as a bureaucratic hassle. This frame echoes employer and agriculture industry claims documented in other studies, namely, the idea that farms and domestic food security would collapse without the SAWP (Weiler et al 2017 ). Such claims of exceptionalism and urgency underpin the premise that unfree labour migration programs are the only means to uphold public goods like food security, and that these programs should consequently be “made even more employer-friendly” (Binford 2013 , p. 193).…”
Section: Resultssupporting
confidence: 72%
“…In addition to workers’ experience of isolation, scholars indicate that structural barriers manifest in their ability to access health services, the quality of care they receive, and in their overall health status. Weiler et al [23] for instance found that workers had limited supports required to access healthy food, which consequently resulted in poor health outcomes for individuals in the South Okanagan. Hennebry et al [22] found that in addition to long working hours and language differences, employer mediation could also have a detrimental impact on workers’ ability to access necessary services in Ontario.…”
Section: Introductionmentioning
confidence: 99%
“…And yet, their arrival and eventual settlement in Manitoba offers a tenuous alternative to much of the scholarship on temporary labour migration globally, and more specifically in Canada. In this literature, the conditions promoted by guest worker programs are routinely and necessarily rehearsed ( Fudge and MacPhail, 2009 ; Nakache and Kinoshita, 2010 ; Sharma, 2012 ; Binford, 2013 ; Strauss and McGrath, 2017 ; Weiler et al, 2017 ). Often prioritized in this critique is the extent to which the value of temporary migrant workers is tied to their exclusion from social, economic, and political life within the host country.…”
Section: Discussionmentioning
confidence: 99%